Impact of colostomy on intestinal microflora and bacterial translocation in young rats fed with heat-killed Lactobacillus acidophilus strain LB - Rigon-Zimmer, K; Mullié, C; Tir-Touil-Meddah, A; Buisson, P; Léké, L; Canarelli, J P (Folia microbiologica, 2008)
A rat animal model of left colostomy was found to significantly impair the growth curve of rats. Assessment of the intestinal flora showed that colostomy mostly affects the cecal but not colonic microflora. Generally, the number of enterococci was increased in both ileum and cecum; cecal lactobacilli also rose, accounting for a promotion of lactic acid bacteria in colostomised rats. No significant differences between colostomised, laparotomised and control rats could be observed for the translocation of intestinal bacteria to internal organs of rats (i.e. spleen, kidneys, lungs or liver), whatever their diet. Heat-killed Lactobacillus acidophilus strain LB administration (dead probiotic bacteria) tended to exhibit a stimulatory effect on bifidobacteria, probably affecting the culture-medium fermentation substances included in the pharmaceutical product. This effect was abolished by laparotomy and colostomy. A trend towards a probiotic-like effect, not susceptible to colostomy, was also witnessed as counts of lactobacilli tended to increase in both cecum and colon of all animals fed with L. acidophilus LB.
Keywords: fyziologie bakterií; střeva; nemoci tlustého střeva; vysoká teplota; Hot Temperature; Intestines; krysa rodu Rattus; Colonic Diseases; modely u zvířat; zvířata; kolostomie; potkani Wistar; Bacterial Translocation; Rats, Wistar; bakteriální translokace; Colostomy; Models, Animal; Rats; Lactobacillus acidophilus; Animals; Bacterial Physiological Phenomena